Magdalena's shaping and reshaping identity in By The Light of My Father's Smile - Sedehi, Kamelia Talebian; Talif, Rosli; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (VEDA Publications, 2014)
Based on Julia Kristeva's concept of speaking subject, the speaking subject has fluid subjectivity. The subject's identity is made and unmade through his use of language and his interaction with other people. Other people's speeches and emotions can influence the subject's subjectivity. The current article will shed light on Alice Walker's By the Light of My Father's Smile in the light of Julia Kristeva's speaking subject, the speaking subject is in the process of being. Alice Walker's novel deals with father's denial of her daughter's sexual desires. In this novel, Magdalena is desconnected from her sexual desires as her father punished her for having an affair with her Mundo beloved. The memory of beating remained in Magdalena's mind and she cannot get rid of it. However, she attempts to use language in order to define her subjectivity. Therefore, this article will focus on the way Magdalena intends to shape her identity by the use of language and interaction with other characters. This article will discuss the way Magdalena uses language and the way she is judged by other characters while they use language and they express their thoughts and emotions about her.